The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/1980-265x-tce-2017-0590
|View full text |Cite
|
Sign up to set email alerts
|

The (Re/De)construction Process of the Professional Identity of Nursing in the Brazilian News Media: 1980-1986

Abstract: Objective: identify how the formulation process of the professional identity of nursing took place through news items related to the regulation of the profession between 1980 and 1986. Method: qualitative, historical, documentary research, guided by the socio-historical research process. Results: of the 2994 news items that were located, 122 were analyzed that had been published in the newspaper Folha de São Paulo. The importance of the movements and claims of the nursing category and its representative or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…10 The importance of performing the role of the nurse in society, and the validation received for that, is a contributing factor in this particular group, which is related to a study in which the importance was investigated of the printed media in the construction of identities in 1980s Brazil, where it is concluded that what is published in the media can revalue or devalue the profession before the community. 12 Although it is true that, during the construction and reconstruction of the professional identity, they were influenced by most immediate factors like family, social origin, and training place, the most important factor in the professional training of the graduate of that period 13 was the socio-historical setting where they shaped such identity, as well as a vital element for the construction of their professional identity, the faculty who served as knowledge mediator in its values, knowledge, and ethical behavior alike, since it constituted an ideal to replicate for those in the process of shaping their own identity.…”
Section: /11mentioning
confidence: 99%
“…10 The importance of performing the role of the nurse in society, and the validation received for that, is a contributing factor in this particular group, which is related to a study in which the importance was investigated of the printed media in the construction of identities in 1980s Brazil, where it is concluded that what is published in the media can revalue or devalue the profession before the community. 12 Although it is true that, during the construction and reconstruction of the professional identity, they were influenced by most immediate factors like family, social origin, and training place, the most important factor in the professional training of the graduate of that period 13 was the socio-historical setting where they shaped such identity, as well as a vital element for the construction of their professional identity, the faculty who served as knowledge mediator in its values, knowledge, and ethical behavior alike, since it constituted an ideal to replicate for those in the process of shaping their own identity.…”
Section: /11mentioning
confidence: 99%
“…It is not permanent and can change over time and with everyday contingencies, as is the case with COVID-19. In this regard, professional identity is (re)constructed from interactions in the work environment and successive socializations, being a continuous process ( 12 - 13 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Ela não é permanente e pode ir se modificando com o tempo e com as contingências do cotidiano, como é o caso da COVID-19. Nesse sentido, a identidade profissional é (re)construída a partir das interações no ambiente de trabalho e sucessivas socializações, configurando um processo contínuo (12)(13) .…”
Section: Introductionunclassified